The CIA book club : the secret mission to win the Cold War with forbidden literature - English, Charlie (Random House, 2025)
"Recounts a covert Cold War operation led by George Minden to smuggle banned literature into Eastern Europe, focusing on the cultural and psychological battle against Soviet censorship and the role underground reading networks played in weakening totalitarian control, especially in Poland"--